2022
DOI: 10.3389/fendo.2022.927959
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Chinese herbal formulas combined with metformin on modulating the gut microbiota in the amelioration of type 2 diabetes mellitus: A systematic review and meta-analysis

Abstract: The effect of Chinese herbal formulas combined with metformin on modulating the gut microbiota in the amelioration of type 2 diabetes mellitus: A systematic review and meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…Metformin has been found to increase the abundance of Lactobacillus in rodents with HFD (Zhou et al, 2016;Bauer et al, 2018). In recent studies, this trend has also been observed in certain clinical studies in patients with T2DM (Xu et al, 2022).…”
Section: Regulation Of Lactobacillus By Metforminmentioning
confidence: 55%
“…Metformin has been found to increase the abundance of Lactobacillus in rodents with HFD (Zhou et al, 2016;Bauer et al, 2018). In recent studies, this trend has also been observed in certain clinical studies in patients with T2DM (Xu et al, 2022).…”
Section: Regulation Of Lactobacillus By Metforminmentioning
confidence: 55%
“…One additional potential causal mechanism through which dietary fibre may influence glycaemic control is through providing substrates for gut microbial fermentation, leading to greater concentrations of SCFAs, which stimulate release of GLP-1, thus improving glycaemic control. A systematic review of dietary interventions [23], some of which could be classed as high fibre diets, on glycaemic control and gut microbial species diversity, composition, and function, in people with T2D found 12 RCTs ranging from 18 days to 3 years in duration. Improvements in HbA1c, fasting blood glucose, total cholesterol, inflammatory markers, and gut microbiota composition from baseline to the end of follow-up were seen within the high fibre intervention groups, but not when compared to the control diets.…”
Section: Fibre and Glycaemic Controlmentioning
confidence: 99%